Analyzing technical and financial benefits of investing in solar plus battery hybrid plants to replace new or aging fossil power plants. - Shalehin , Musfec-Us-; Mandal, Shuvra (My University, 2026)
The increasing environmental impact of entirely fossil fuel-based power generation, rising fuel tariffs, and growing power conservation concerns have multiplied the worldwide transition to renewable power system. In Bangladesh, electricity generation is based closely on getting traditional fossil fuel like natural gas, oil, and coal. This paper addresses the alternative of three distributed fossil fuel generators supplying industrial electricity by designing a grid-interactive PV–battery energy system (BESS). In MATLAB/Simulink a 60 kW PV-based prototype system was first designed to observe power electronic performance, battery charging and discharging behavior, voltage regulation, reactive and active power, and system stability under real-time irradiance profile and load conditions. The equivalent hybrid system was then optimized within the NREL REopt platform to evaluate fossil fuel displacement, where it was modified to serve the same commercial load currently fed through three generators. Eleven scenarios representing specific plan cost structures, flexibility requirements, and deployment assumptions were analyzed to determine the most optimal appliance sizes, renewable energy penetration, and life-cycle economics. The results show that the designed solar PV–BESS equipment can reliably upgrade fossil fuel generators to maintain continuous energy supply, realize near-perfect renewable energy penetration, reduce operating cost and emissions, and transform the levelized cost of energy. The precise low-cost regional scenario in 2030 resulted in a first-class overall performance, resulting in almost 100% renewable energy supply with a predicted LCOE of almost 0.0357 USD/kWh. Overall, the findings show that the proposed PV–BESS hybrid equipment can successfully replace the current distributed fossil fuel generation with a technically robust and economically feasible renewable energy alternative.
Keywords: renewable energy sources; solar energy; emissions; energy technology; reactive power; power electronics; electrical power networks; fossil fuels; charging (loading); hybrid technology; fi=Energiatekniikka|en=Energy Technology|; Master’s Programme in Electrical and Energy Engineering